Local development plans: approaches and trends in Latin America - Díaz Malásquez, Luis René (2002)
The current study shows the urgent need in the management and planning of local and regional authorities in the development of their constituencies governments. The importance in developing strategic plans and vision development with new approaches and trends prevailing in the global world. Sustainable development, human development and Agenda 21, are paradigms and / or development models that focus the present study, in order to obtain sustainable cities and towns, with a working document as Agenda 21 and achieving development its human inhabitants.